Fabrication and characterisation of Frequency Selective Surface (FSS) for Terahertz Sensing Application. Issue 1 (1st April 2022) - Ishak, N S; Zainal, N; Seman, F C; Shah, S M
Abstract: A frequency selective surface (FSS) structure based on a circular slot with 28 to 31 μm was fabricated using Electron Beam Lithography combined with wet etching technique on a 400 μm thick quartz substrate. The circular slot pattern, designed using the CST software, was transferred during the Electron Beam (EBL) exposure with 100 kV voltage acceleration, 2 nA of e-beam current, and line dosage of 1000 μC 2 . A 0.5 μm thick aluminium layer was deposited on a quartz substrate using the thermal evaporator technique. The aluminium thickness was confirmed by laser microscope and surface profiler measurement. The investigation shows that 20 seconds is the optimal etching time for producing the desired FSS circular slot structure compared to 40 and 60 seconds. The fabricated samples surface metrology was examined using an optical microscope, Field Emission Scanning Electron Microscope (FESEM) and Atomic Force Microscope (AFM). The material compositions of the samples were confirmed by using the Energy Dispersive X-ray (EDX) measurement. Results show that, on average, there are ±1.5 μm of tolerance produced for fabricated sample size on the circular slot pattern compared to the CST simulation results. FSS performance slightly shifted in the frequency from actual 1.80 THz to 1.79 THz, whereas the transmission magnitude has increased by 0.03 from 0.91 to 0.94.